The Synthesis of Polyaniline/Fe3O4 to Removal of Lead Ions from Water and Wastewater Samples - Ali Shokouhi Rad (آب و فاضلاب, 2020)
Due to the importance of removing heavy ions from water samples, in the present study, a magnetic nanocomposite based on Fe3O4 particles coated with polyaniline was developed and evaluated as a strong adsorbent to remove lead (II) ions from water and effluent samples. In order to characterize the nanocomposite, the transmission electron microscope was used to determine the exact size of the nanoparticles and the BET technique was used to determine the effective surface of adsorbent and also the CHNS and TGA analyses were used to confirm the coating of Fe3O4 magnetic nanoparticles with polyaniline and the survey of the thermal stability of nanocomposite, respectively. The flame atomic absorption spectroscopy was used to determine the values of lead ions in the solution. Characteristics affecting lead ion removal including pH, adsorbent value and contact time at different temperatures were optimized. Optimal values of pH and adsorption rate and contact time for 100 ml of solution with an initial concentration of 50 ppm were obtained in the pH of 9, 3 mg adsorbent, and contact time of 60 minutes, respectively. Equilibrium data from adsorption studies showed that the Langmuir isotherm showed better results than the Freundlich isotherm. Also, the maximum lead adsorption capacity (II) on Polyaniline/Fe3O4 nanocomposite was 114.9 mg of lead per gram of adsorbent.